Tamoxifen treatment in breast cancer: diagnostic methods for endometrial changes - Kamińska, Aleksandra I.; Piecak, Karolina; Milart, Paweł; Czuczwar, Piotr; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2025)
The aim of the study was to review publications on the early, most accurate diagnosis of pathological changes in the endometrium, which occur during and after tamoxifen (TAM) therapy for breast cancer (BC). Accurate diagnosis of potential endometrial lesions is essential to make correct decisions regarding the necessity of adjuvant therapy with TAM. MEDLINE (http://www.ncbi. nlm.nih.gov/pubmed), EMBASE (http:// www.embase.com) and Scopus (http:// www.scopus.com) databases were searched using the following MeSH terms in titles and abstracts: (“tamoxifen endometrial hyperplasia” OR “tamoxifen endometrial pathology” OR “endometrial pathology tamoxifen”). No language restriction was used in the literature search. The search was limited to studies in humans. The results of an ultrasound investigation of the endometrium in asymptomatic BC patients receiving TAM should be interpreted with caution. An overdiagnosis of endometrial abnormalities, and the consequent unnecessary invasive diagnostic procedures could discourage some patients from continuing the adjuvant treatment with TAM, putting them at increased risk of recurrent BC. There is no evidence that patients receiving adjuvant TAM therapy could benefit from a screening program based on the ultrasound examination alone. Asymptomatic BC patients on adjuvant TAM-treatment should not be submitted routinely to ultrasound examination or biopsy, but encouraged to report any abnormal vaginal bleeding promptly.